Volume 2D: Turbomachinery 2016
DOI: 10.1115/gt2016-56683
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Low Specific Speed Centrifugal Compressor Research Facility

Abstract: To achieve aggressive specific fuel consumption goals, aircraft engines are tending toward higher overall pressure ratios and higher bypass ratios for turbofans. As sizes decrease to meet these requirements, centrifugal compressors become a viable option as the last stage of the high pressure compressor. The last stages of an axial compressor in a small core engine face reduced efficiency due to the relatively large tip clearances with respect to blade height, and therefore, it may be more appropriate to finis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Additional details on this facility including a normalized compressor map can be found in Ref. [12]. A graphical representation of the research compressor is presented in Fig.…”
Section: Experimental Facilitymentioning
confidence: 99%
“…Additional details on this facility including a normalized compressor map can be found in Ref. [12]. A graphical representation of the research compressor is presented in Fig.…”
Section: Experimental Facilitymentioning
confidence: 99%
“…The test facility capabilities, geometric details, and baseline performance data are given in Ref. [21]. The design rotational speed of the impeller is 22,500 rpm, and it operates at engine-representative Mach numbers.…”
Section: Test Compressormentioning
confidence: 99%
“…The compressor mass flow rate is controlled via a throttle valve installed in the primary exhaust line routed to ambient. Full details of the research facility can be found in [21].…”
Section: Experimental Facilitymentioning
confidence: 99%